Microwave remote sensing of cloud liquid water and surface emittance over land regions - Jones, Andrew S., author; Vonder Haar, Thomas H., author; Cooperative Institute for Research in the Atmosphere (Fort Collins, Colo.), publisher (Colorado State University. Libraries, 1989)
Microwave remote sensing of cloud liquid water has largely been limited to areas over ocean surfaces. This study uses data from a new microwave instrument, the SSM/I on a polar-orbiting DMSP satellite, and infrared and visible data from the VISSR instrument on the GOES satellite in geostationary orbit. The region selected for the study was an area of 500 km x 500 km centered on northeast Colorado during the first week of August 1987. The SSM/I instrument has new high frequency channels (85.5 GHz) which are more strongly attenuated by cloud liquid water than channels on previous instruments. This allows for the estimation of integrated cloud liquid water based on the microwave brightness temperature depression caused by attenuation and emission of microwave radiation at the colder cloud levels. Atmospheric attenuation due to oxygen and water vapor is determined using a millimeter-wave propagation model (MPM). The Rayleigh approximation is used for the calculation of cloud liquid water attenuation. Surface emittance measurements at the SSM/I frequencies were made with the aid of co-located GOES infrared data during clear sky conditions. Images produced of the retrieved surface emittances suggest a strong influence by wet surfaces caused by precipitation and irrigation. Error analysis results indicate absolute errors of ±0.012 for surface emittance retrievals for the 85.5 GHz channels. Integrated cloud liquid water retrievals show good qualitative agreement with other available data sources. Numerical error sensitivity analysis and comparison of integrated cloud liquid water retrievals for the vertical and horizontal polarizations show error estimates of 0.15 kg•m-2 including instrument noise. A bias between the horizontal and vertical polarizations of the 85.5 GHz channels was noticed in the retrieved integrated cloud liquid water amounts. The bias appears to be due to a relative instrument error between channels of approximately 1.5 K. Absolute error estimates of the integrated cloud liquid water retrievals are unavailable but calibration of the method should be possible if quantitative integrated cloud liquid water amounts are known.
January 1989.
Keywords: Microwave remote sensing; Clouds -- Colorado; Condensation (Meteorology)